Empowerment of human resources in the plantation sector in Tegalsari Hamlet, Magelang Regency - Fitriana Yuliastuti; Devi Pujiyanti; Laela Safitri; Azizah Nur Rafa K. A.; Fadhil Lutfian; Bagus Sampurno; Zulfikar Bagus Pambuko; Lintang Muliawanti (Universitas Muhammadiyah Magelang, 2022)
It is necessary to develop community empowerment initiatives in the Covid era, one of which entails holding workshops on the use of garden medicinal herbs. Socialization and workshop in this program is aimed at increasing the empowerment of rural communities in optimizing garden yields and independent, creative, and innovative entrepreneurship for the people of Dusun Tegalsari. When evaluation and monitoring were carried out a month following the program, the training activities went smoothly and successfully. As a result, there is an increase in public knowledge of the use of medical plant cultivation to boost income through the development of new products.